Antioxidants in food systems. Mechanism of action - Polumbryk, Maksim; Ivanov, Sergey; Polumbryk, Oleg (My University, 2013)
The mechanisms of action of natural and synthetic antioxidants in food systems including lipids, proteins and carbohydrates have been discussed. It is essentially important and may predict the antioxidants effectiveness in the processes of food storage. The main benefits of industrial antioxidant utilization were considered. The most attention was given to the antioxidants mixtures and most effective synergists.
Keywords: харчові системи; free radicals; food systems; photosensitizations; food storage; antioxidants; окиснення; вільні радикали; фотосенсибілізатори; зберігання продуктів; антиоксиданти; кафедра екології та екоменеджменту; кафедра харчової хімії; кафедра експертизи харчових продуктів